Effect of Diabetes in Blood Dilution and Angle of Rotation on the Output Power of Second Harmonic Generation of Nd: YAG Laser - Mohammed, Mohammed F (Al-Nahrain Journal of Science, 2012)
Glucose monitoring is a crucial factor for diabetic self management. Widely used technologies require the use of fresh blood samples in special test strips. This is expensive and does not lend it self to continuous monitoring. An alternative method of measuring blood glucose levels optically is investigated. This method is called “Optical Activity”. It’s able to determine glucose concentrations with varying degrees of sensitivity and ranges of applicability. This method is used to determine the angle of rotation for different glucose concentrations when the laser beam passing through the samples of blood. In this research, a green laser of second harmonic generation (SHG) of Nd: YAG with measured maximum output power 55 mW and wavelength of 532 nm was used. The output power of laser beam which was passing through the glass cuvette of blood with diabetes was measured as a function of calculated specific rotation angle for different concentrations of the diluted blood and also the output power of laser beam which was passing through the glass cuvette of blood with null diabetes was measured. These results of two samples are reported and the implications for possible new monitoring strategy are considered. Thus, the person can be specified his blood contain the diabetes or not.